Incidence of ophthalmic manifestations in congenital cytomegalovirus (CMV) - Jennifer L. Rossen; Abdelhamid Hindi; Safa Rahmani; Brenda L. Bohnsack (BMC Ophthalmology)
Abstract Background Congenital cytomegalovirus (CMV) infections are associated with eye manifestations, especially in patients with systemic disease. However, there are no ophthalmic screening guidelines for infants with congenital CMV. Methods Retrospective review of pediatric patients (< 18 years old, 2010–2023) with a diagnosis of congenital CMV and at least 1 eye examination. Gestational age at birth, systemic findings, and ophthalmic findings at initial and final eye examinations were collected. Results Seventy-two patients (47% male) with congenital CMV underwent initial eye examination at 2.1 ± 2.9 years of age (median 0.3 years). Thirty-one patients (43%) only had one eye examination while 41 patients had follow-up (1 month-19 years). Fifty-two patients (72%) had systemic findings, most commonly hearing loss (50%), neurologic abnormalities (39%), and developmental delay (38%). Patients born < 36 weeks gestation (n = 15) had a higher rate of systemic findings, neurologic abnormalities, developmental delay, and intrauterine growth restriction compared to full-term patients. Twenty-four (33%) patients had ocular findings and all also had systemic manifestations. Strabismus (26%) and optic nerve abnormalities (17%) were most common. Only 2 patients (3%) were diagnosed with retinitis, which was detected at initial examination. Conclusions One-third of patients with congenital CMV had ocular findings in conjunction with systemic manifestations. Retinitis was rare and detected on initial eye examination. While initial screening for retinitis is important, patients with systemic sequelae of congenital CMV are at risk for other eye manifestations and require continued follow-up.